(3OjhGf GdJdYaQis - (3GdJdYaQj , eMeO Hf jhSa Hf eSYhO GdTjHGfj, TgGH GdOjf CHh YHO Gddg,J (B675 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdhGMO GdbOje CeG HYO aEf GddZGJ hCLd efWb GdCdSf GdeNJdaGJ GdbQBf GdeLjO hGfg dcJGH YRjR dG jCJ GdHGWd ef Hjf jOjg hdG ef Ndag ebOeI GdcJGH aUd ai GdJUQja s
(3BNQgG (B:s
(3GdJaGYd ef JTGCe GdQLd EPG CNP aMh GdTGCe Je GdQHY GdKGfi ef cJGH TeS GdYdhe GfJgi HMeO Gddg GdhGMO Gd Mi Gdbjhe s
(3GdfSNI HgG MhGTs
(3ZjQ eQJH Ydi GdbhGai Ch GdehVhYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B25s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B780s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs